2003
DOI: 10.1099/mic.0.25807-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutation rates: estimating phase variation rates when fitness differences are present and their impact on population structure

Abstract: Phase variation is a mechanism of ON-OFF switching that is widely utilized by bacterial pathogens. There is currently no standardization to how the rate of phase variation is determined experimentally, and traditional methods of mutation rate estimation may not be appropriate to this process. Here, the history of mutation rate estimation is reviewed, describing the existing methods available. A new mathematical model that can be applied to this problem is also presented. This model specifically includes the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 33 publications
(19 reference statements)
2
46
0
1
Order By: Relevance
“…There are several approaches to estimating rates of phenotypic or genotypic switching. A theoretical paper that deals with some complexities and interpretative issues when measuring switching rates was recently published (Saunders et al, 2003). However, the key issue in our study is whether the observed rates of switching reflect differences, even if these estimates would need to be modified to better reflect an estimate of mutation rates.…”
Section: Discussionmentioning
confidence: 67%
“…There are several approaches to estimating rates of phenotypic or genotypic switching. A theoretical paper that deals with some complexities and interpretative issues when measuring switching rates was recently published (Saunders et al, 2003). However, the key issue in our study is whether the observed rates of switching reflect differences, even if these estimates would need to be modified to better reflect an estimate of mutation rates.…”
Section: Discussionmentioning
confidence: 67%
“…These mutations are most likely to occur in global regulatory genes. This variation or phenotypic conversion is known to occur in many bacterial species in order to generate population diversity thought to be important for niche adaptation (32). Interestingly, the TofR AHL receptor of strain ATCC 33617…”
Section: Discussionmentioning
confidence: 99%
“…À1 -10 À2 per generation (Saunders et al 2003). This is not the case for [PSI1], for which the reverse epimutation rate (loss of [PSI1]) is ,2 3 10 À4 (Tank et al 2007).…”
mentioning
confidence: 94%